2021
DOI: 10.3390/vaccines9050424
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of COVID-19 Vaccination among Front-Line Health Care Workers: A Nationwide Survey of Emergency Medical Services Personnel from Germany

Abstract: Introduction: The aim of this study was to evaluate the COVID-19 vaccination acceptance of emergency medical services (EMS) personnel as front-line health care workers (HCW) in Germany. Several studies have shown low willingness for vaccination (e.g., seasonal influenza) among HCWs and EMS personnel. Methods: We created a web-based survey. The questions were closed and standardized. Demographic data were collected (age, sex, federal state, profession). Experience with own COVID-19 infection, or infection in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 59 publications
7
63
1
6
Order By: Relevance
“…No significant differences were observed in vaccine effectiveness across genders at any dose and for any outcome. This finding is in line with previous trials and real-world studies on healthcare workers [3,4,14], and may help, at least in part, to shorten the gap in vaccine hesitancy between males and females, the latter having shown higher reluctancy in several surveys [14,[26][27][28][29]. Beyond effectiveness, however, the potential reasons behind female hesitancy could be the lower COVID-19 lethality [2,16], and especially the substantially higher rates of adverse events among vaccinated women [23,30].…”
Section: Discussionsupporting
confidence: 86%
“…No significant differences were observed in vaccine effectiveness across genders at any dose and for any outcome. This finding is in line with previous trials and real-world studies on healthcare workers [3,4,14], and may help, at least in part, to shorten the gap in vaccine hesitancy between males and females, the latter having shown higher reluctancy in several surveys [14,[26][27][28][29]. Beyond effectiveness, however, the potential reasons behind female hesitancy could be the lower COVID-19 lethality [2,16], and especially the substantially higher rates of adverse events among vaccinated women [23,30].…”
Section: Discussionsupporting
confidence: 86%
“…After the 10 March 2021, 59% of respondents to the poll were already vaccinated against COVID-19, versus 46% in the national surveillance of French healthcare workers [ 15 ]. Since mid-2020, 15 studies investigated the willingness, and 3 reported the scaling-up of COVID-19 vaccination among healthcare professionals [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Taken together, we can estimate the overall willingness to get vaccinated at 65% (95CI 56% to 73%) among healthcare workers, with a prediction interval ranging from 18% to 94%, and varying by region of the globe ( Supplementary Figure S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trust in vaccines, positive emotions, and locus of control were high predictors of recommendation; some research has shown that age, as a factor capable of affecting perceived risk, inversely influences fear and hesitation in vaccines in healthcare personnel [27][28][29]; however, the results on the present sample confirmed a more positive perception and greater confidence in the vaccines of younger healthcare professionals [30]. Future research will have to clarify exactly the role of age concerning the various variable trusts, recommendations, hesitancy, and fear for vaccine.…”
Section: Discussionmentioning
confidence: 99%